Age-Appropriate Digital Channels - Darvishy, Alireza; Hutter, Hans-Peter.; Seifert, Alexander (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2022)
As a client or a developer, what do you need to consider when developing an age-appropriate website or mobile application? This book explains how age-related limitations affect the use of websites and mobile applications. If gerontological aspects are not taken into account in the design of digital channels, older people tend to do without them. Therefore, websites and mobile applications need to take into account the needs of older people. In the book, you will find useful recommendations on how to do this so that your websites and mobile apps are easy to use for everyone. The content Age-specific characteristics and difficulties in using websites and applications Recommendations for the implementation of websites and mobile applications The authors Prof. Dr. Alireza Darvishy is Professor of Computer Science with specialisation in ICT accessibility at the Zurich University of Applied Sciences (ZHAW) and adjunct Professor at Isfahan University of Technology. Prof. Dr. Hans-Peter Hutter is Professor of Computer Science with specialisation in human-computer interaction and speech-based user interfaces at the ZHAW. Dr. Alexander Seifert is Head of Research at the Centre for Gerontology at the University of Zurich.
Introduction -- Age-appropriate website design -- Age-appropriate mobile applications -- Conclusion and implementation.
Keywords: Software engineering; Interactive multimedia; Multimedia systems; Ethics; Mass media-Moral and ethical aspects; Software Engineering; Media Design; Moral Philosophy and Applied Ethics; Media Ethics